2015
DOI: 10.1111/jpi.12260
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin regulates the transcription of βAPP‐cleaving secretases mediated through melatonin receptors in human neuroblastoma SH‐SY5Y cells

Abstract: Melatonin is involved in the control of various physiological functions, such as sleep, cell growth and free radical scavenging. The ability of melatonin to behave as an antioxidant, together with the fact that the Alzheimer-related amyloid β-peptide (Aβ) triggers oxidative stress through hydroxyl radical-induced cell death, suggests that melatonin could reduce Alzheimer's pathology. Although the exact etiology of Alzheimer's disease (AD) remains to be established, excess Aβ is believed to be the primary contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 80 publications
1
44
0
Order By: Relevance
“…Our previous studies showed that melatonin stimulated nonamyloidogenic processing of βAPP by enhancing the expression of ADAM10 and downregulated the amyloidogenic processing secretases BACE1 and PS1 . To investigate the protective effects of melatonin in pathogenic neurotoxic conditions induced by Aβ 42 treatments, cells were pretreated with various concentrations of melatonin (0.01, 0.1, and 1 μmol/L) 1 hour prior to Aβ 42 (1 μmol/L) treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that melatonin stimulated nonamyloidogenic processing of βAPP by enhancing the expression of ADAM10 and downregulated the amyloidogenic processing secretases BACE1 and PS1 . To investigate the protective effects of melatonin in pathogenic neurotoxic conditions induced by Aβ 42 treatments, cells were pretreated with various concentrations of melatonin (0.01, 0.1, and 1 μmol/L) 1 hour prior to Aβ 42 (1 μmol/L) treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic benefits of melatonin in MCI and AD patients, animal, and aging models along with the restoration of memory deficits have been substantially documented. Our previous studies delineated novel mechanisms of melatonin regulation of βAPP‐processing secretases under physiological conditions . However, to unveil the underlying molecular mechanisms of melatonin regulation under pathological conditions requires further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that melatonin is able to interact with Aβ‐40 and Aβ‐42 and reduce neuronal damage by inhibiting the progressive formation of β‐sheets and amyloid fibrils in vitro . By regulating several crucial protein kinases including nuclear factor‐κB kinase (pNF‐κB), cyclin‐dependent kinase 5 (cdk5) and activated glycogen synthase kinase‐3β(GSK‐3β), melatonin attenuates hyperphosphorylation of tau and decreases Aβ accumulation …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that melatonin elevates ADAM10 level in HEK293 and neuronal SH-SY5Y cells via G protein-coupled receptor-induced PKC/Erk activation (Panmanee et al, 2015; Shukla et al, 2015). This effect seems to depend on human ADAM10 promoter region −1193 to −555 as a respective deletion construct failed to respond in a reporter gene assay (Shukla et al, 2015).…”
Section: Regulation Of Adam10mentioning
confidence: 99%
“…Finally, as melatonin seems to be able to increase the level of deacetylase in young and aged primary neurons (Tajes et al, 2009), the observed induction of ADAM10 by melatonin (Panmanee et al, 2015; Shukla et al, 2015) might also rely on deacetylase activation.…”
Section: Regulation Of Adam10mentioning
confidence: 99%